The Impact of Health Policy on Community-Based Palliative Care Services: A Mixed-Methods Evaluation in Bandung, Indonesia - Dea Albertina; Istiqomah Putri; Nazeera Hamid; Cindy Susanti (Community Medicine and Education Journal, 2025)
Palliative care is a crucial component of comprehensive healthcare, yet access to community-based palliative care services remains limited in many low- and middle-income countries, including Indonesia. This study aimed to evaluate the impact of existing health policies on community-based palliative care in Bandung, Indonesia. A mixed-methods approach was employed, combining quantitative and qualitative data collection and analysis. Quantitative data included a retrospective analysis of patient records (n=350) from three community-based palliative care providers in Bandung from 2018-2023, assessing referral patterns, service utilization, and patient demographics. Qualitative data were gathered through semi-structured interviews with policymakers (n=10), healthcare providers (n=15), and patients/caregivers (n=20) to explore their perspectives on policy implementation and its impact. Data were analyzed using descriptive statistics, thematic analysis, and a framework approach guided by the WHO Health Systems Framework. The study found that while national health policies acknowledge the importance of palliative care, significant gaps exist in implementation at the local level. The number of patients accessing community-based palliative care increased modestly from 45 in 2018 to 78 in 2023, but this represents a small fraction of the estimated need. Key policy-related barriers identified included: limited funding allocated specifically for community-based palliative care , inadequate training and workforce capacity in palliative care, lack of standardized referral pathways from hospitals to community-based services and limited public awareness of palliative care. In conclusion, health policies in Indonesia have not yet translated into widespread access to quality community-based palliative care in Bandung. Strengthened policy implementation, increased funding, workforce development, improved referral systems, and enhanced public awareness are crucial to address this gap and improve the quality of life for patients with life-limiting illnesses and their families.